Floral structure and genetical differences of sandalwood variants in Gunung Sewu (Java, Indonesia), and its effects on breeding systems and reproductive ability - YENI W.N. RATNANINGRUM; AFFAN KURNIAWAN (Biodiversitas Journal of Biological Diversity, 2019)
Ratnaningrum YWN, Kurniawan A. 2019. Floral structure and genetical differences of sandalwood variants in Gunung Sewu (Java, Indonesia), and its effects on breeding systems and reproductive ability. Biodiversitas 20: 393-404. Our preliminary studies reported that the failure on rehabilitation program of sandalwood, an endangered endemic species in Indonesia, was caused by low viability and survival due to reproductive failure. New sandalwood landraces in Gunung Sewu Geopark, Java island consist of three variants (YBF, refers to "yellow big flower"; RBF, "red big flower"; and RSF, "red small flower") differed by floral structures. This study was made on three sandalwood variants grew in four landraces representing landscape zones in Gunung Sewu, from April to September 2017 flowering season. This advanced study was aimed to estimate the differences in floral structures and genetic diversity among variants, and their effects on breeding systems and reproductive ability. Floral organ measurements were made on each variant. Isoenzyme analysis was conducted to estimate the genetic diversity of each variant and in each site. Mating systems were estimated by Index of Incompatibility (ISI) and Cruden's Out Crossing Index (OCI) methods. Reproductive ability was measured by counting Pollination Effectiveness, Reproductive Success and seed viability. Results found that six loci were polymorphic in most of sites and variants, with exception for Petir and Bejiharjo sites and YBF variant. Observed heterozygosity varied with sites but was similar among variants. Some of diversity existed among both sites and variants. The OCI value scored more than 3 for all variants, indicating an outbreeding mating system. RSF showed higher OCI value compared to both RBF and YBF. Bleberan and Nglanggeran, the outcrossed and completely self-incompatible populations (ISI = 0), failed to produce selfed seeds. In such highly outcrossing, self-incompatible populations, the highest seed set was gained from intraspecific-crossed pollination. Contrastly, the inbreeding and self-compatible populations (ISI = 3 to ?), Petir and Bejiharjo, tended to alter its matting system to be more inbreeding. Reproductive ability differed by sites but was similar among variants.